Intelligent agents and risk based model for supply chain management - Smeureanu, Ion; Ruxanda, Gheorghe; Diosteanu, Andreea; Delcea, Camelia; Cotfas, Liviu Adrian (Technological and Economic Development of Economy, 2012)
This paper presents a software agent based framework’s architecture for boosting performance in supply chain management applications. The framework is based on agent interaction and semantic web service composition. The purpose of such a platform is to develop flexible business applications for SCM transactions modeling, in collaborative and distributed economic systems. The interaction between agents is limited by a cybernetic model that takes into account several constraints one of the main being bankruptcy risk potential of the peer partner company.